Formulation, Development, Optimization and In-Vitro Anthelmintic Evaluation of Polyherbal Pills - Prashant, Pawar; Shivraj, Mane; Padmaja, Kore; Jayram, Shinde; Dipak, Taur; Vaidehi , Govekar; Kirti, Thorat (International Journal of Aquatic Research and Environmental Studies, 2026)
Parasitic helminth infections remain a significant global health burden, particularly in developing regions with poor sanitation infrastructure. While synthetic anthelmintic drugs such as albendazole are commonly used, emerging drug resistance and adverse effects have prompted renewed interest in herbal alternatives. This study aimed to formulate, optimize, and evaluate polyherbal pills utilizing traditional medicinal plants for in vitro anthelmintic activity. Polyherbal pills were formulated using Embelia ribes (Vavding), Piper nigrum (Black Pepper), Helicteres isora (Murad Sheng), Ferula asafoetida (Hing), and Black Salt (Kala Namak), with gum acacia as a binder. The formulation was evaluated for physicochemical parameters (friability, hardness, disintegration time, weight variation, dissolution rate) and in vitro anthelmintic activity against Pheretima posthuma at concentrations of 12.5, 25, 50, 100, and 200 mg/mL, using albendazole as the standard reference drug. The polyherbal pills demonstrated acceptable pharmaceutical properties: friability 0.66%, mean hardness 5.28 kg/cm², disintegration time 27-31 min, and weight variation within ±5%. The formulation exhibited dose-dependent anthelmintic activity. At 200 mg/mL, the mean time of paralysis was 9.68 ± 0.30 min and time of death was 13.55 ± 0.43 min. While the standard albendazole (50 mg/mL) showed faster activity (paralysis: 11.36 ± 0.36 min; death: 19.77 ± 0.43 min), the polyherbal formulation demonstrated comparable efficacy at higher concentrations with statistical significance (P < 0.001). The developed polyherbal pills represent an effective, safe, and stable alternative therapeutic option for helminth infections, successfully bridging traditional herbal knowledge with modern pharmaceutical optimization techniques.
Keywords: Polyherbal formulation; Anthelmintic activity; Embelia ribes; Piper nigrum; Helicteres isora